EXPERIMENTAL EVALUATION AND VIBRATION RESPONSE MODELLING OF CYLINDRICAL ROLLER BEARING SUBJECTED TO STATIC LOAD AND RESIDUAL UNBALANCE - WAYAN ADISAPUTRA (NIM :23107024); Pembimbing : Prof. Dr. Ir. Komang Bagiasna, I
Rolling bearing has an important role on machineries for supporting the rotating elements. The forces act on a bearing can be in form of static forces and dynamic forces which can yield vibration on bearing housing. In this case the investigation was carried out on cylindrical roller bearing. Vibration response analysis of cylindrical roller bearing subjected to static load and residual unbalance loads is being conducted. Refering to the measured bearing vibration, theoretical model was developed to explain its vibration mechanism and its origin as well. The experimental part of this research consists of FRF (Frequency Response Function) measurements to obtain dynamic characteristics of the bearing house and the vibration response on the bearing house. Shaft speed and static load are being varied stepwise from 300Rpm to 1200Rpm with step interval of 300Rpm while the static load are varying by 200N, 400N, and 600N. The measured vibration response shows, BPFO frequency and its harmonics as well as 1xRpm sideband frequencies. Based on the results, an analytical model was developed covering the static as well as the residual unbalance loads with the objective to reveal the vibration source. The analytical model shows the same vibration signatures as the experimental results. The differences between the model and the experimental results are the magnitude of the dominating frequency and the number of sidebands. Overall the analytical model can reveal the mechanism and the source of the dominant frequency appears on the experimental results.